Sociology Matters - T. Schaefer Richard (McGraw-Hill Humanities, 2007)
Richard Schaefer's Sociology Matters is a very concise introduction to the discipline of sociology. Its straightforward style, streamlined design, and highly focused coverage make it the perfect short, affordable, introductory text for instructors who use a variety of materials in their course. Sociology Matters helps students understand and connect to the topics it covers by answering the question "How does sociology matter?"